Law and macroeconomics legal remedies to recessions - Listokin, Yair, 1975- (Harvard University Press, 2019)
Law and Macroeconomics is among a small number of books to explore law, regulations, and macroeconomics. Most of law and economics is focused on microeconomics. In contrast, Listokin is interested in macroeconomic policy, and especially the question of what legal and regulatory options are there to quickly respond to a crisis like the Great Depression or the recent Great Recession. To make this manageable, Listokin focuses on the role of law in confronting the 2008 financial crisis. In the economist's toolkit for confronting a recession are choices such as lowering interest rates and "quantitative easing." The law offers no such toolkit. Listokin argues that it should, especially given how modest the economic fixes have been since 2008.--